Teaching, researching and innovation: An appetising programme. (March 2016) - Notten, Ton
This article is a follow-up to, or even a sharpening of, a presentation I offered, three years ago, in this journal TPA, about the closely related research-and-innovation-enrichment of the profession of mid-career students within their two-year part-time master's course. I wrote then about my 12 years of experience at the Urban Education Masters Programme and about my research work at the Rotterdam University of Applied Sciences. At the end of that article I introduced a Möbius strip metaphor, which expresses a teaching-and-researching chain, a strip which keeps unclear when and where teaching comes to an end and researching starts (and the reverse), or: 'the conviction that a vivid and enriching two-way traffic offers good opportunities to strengthen both the students' research skills and their reflective and innovating capacities' (Notten, 2013a: 78–79). And then, in November 2013, a more than 'very interesting' advisory report was published by the Dutch Scientific Council for Government Policy (WRR) which argues how dealing with dependencies, knowledge circulation and lifelong learning can be regulated better as they are vital preconditions for future sustainable competitiveness and for better results in the public sector. After summarising that very inspiratory WRR report, I will introduce another even more fruitful metaphor, I hope. A multi-levelled one about how to renew conditions for social intervention science.